2006
DOI: 10.1016/j.jacc.2005.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone Improves Myocardial Perfusion in Postmenopausal Women With Ischemic Heart Disease

Abstract: In postmenopausal women with ischemic heart disease, six months of therapy with tibolone significantly improved stress myocardial perfusion and the "amount of ischemia."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…From these alternatives of HRT, only the effect of tibolone on the microcirculation has been explored by nuclear imaging. In a recent pilot study (61), 6 months of treatment with tibolone decreased the extent and severity of myocardial perfusion defects during stress as well as the ‘amount of ischaemia’ in postmenopausal women with IHD, as assessed by SPECT imaging. Whether such improvement in the ‘amount of ischaemia’ after tibolone therapy reduces clinical coronary events needs to be determined.…”
Section: Effects Of Hormone Replacement Therapy On Coronary Vascular mentioning
confidence: 99%
“…From these alternatives of HRT, only the effect of tibolone on the microcirculation has been explored by nuclear imaging. In a recent pilot study (61), 6 months of treatment with tibolone decreased the extent and severity of myocardial perfusion defects during stress as well as the ‘amount of ischaemia’ in postmenopausal women with IHD, as assessed by SPECT imaging. Whether such improvement in the ‘amount of ischaemia’ after tibolone therapy reduces clinical coronary events needs to be determined.…”
Section: Effects Of Hormone Replacement Therapy On Coronary Vascular mentioning
confidence: 99%
“…There was, however, evidence that T may possess anti-ischemic effects. Indeed, a prospective randomised open-label pilot study performed in PMW with ischemic heart disease demonstrated that 6 months of T significantly improved stress myocardial perfusion defects, as well as the 'amount of ischemia' as assessed by SPECT imaging [59]. Thus, T may exert a favourable effect on CV secondary prevention by improving myocardial perfusion in PMW with cardiac perfusion defect.…”
Section: Peripheral and Coronary Arteriesmentioning
confidence: 99%
“…More recently, a prospective randomized open-label pilot study was performed in 26 postmenopausal women not on HRT referred for a clinically indicated single-photon emission computed tomography (SPECT) myocardial perfusion study with stress-induced perfusion defects (Campisi et al 2006). All had cessation of menses ≥1 year, a normal mammogram, breast and pelvic examinations and pap smear within 6 months of the study.…”
Section: R Campisi and F D Marengomentioning
confidence: 99%